Formal methods: foundations and applications 13th Brazilian Symposium on Formal Methods, SBMF 2010, Natal, Brazil, November 8-11, 2010, Revised Selected Papers - Davies, Jim; Silva, Leila; Simao, Adenilso (Springer, 2011)
This book constitutes the thoroughly refereed post-conference proceedings of the 13th Brazilian Symposium on Formal Methods, SBMF 2010, held in Natal, Brazil, in November 2010. The 18 revised full papers were carefully reviewed and selected from 55 submissions. The papers presented cover a broad range of foundational and methodological issues in formal methods for the design and analysis of software and hardware systems as well as applications in various domains.